Predictions from Three Data Sources - Naturalistic Home Observation, Ratings, Experimental Situation - in the Area of Child Compliance - Lytton, Hugh. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
A report is presented of the findings of an investigation into the development of compliance, dependence and independence of two-year-old boys in the context of parent-child interaction, as well as in relation to genetic factors. The three techniques used in assessing children's and parents' characteristics and for studying the parent-child interaction were naturalistic home observation, ratings, and an experimental playroom situation. Data were analyzed by computer to yield counts of certain types of behavior. Results are inconclusive. (CK)
Sponsoring Agency: Canada Council, Ottawa (Ontario).
ERIC Note: Paper presented at the biennial meeting of the Society for Research in Child Development (Philadelphia, Pennsylvania, April 1, 1973).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Patterns; Behavior Rating Scales; Genetics; Interaction Process Analysis; Males; Observation; Parent Child Relationship; Parent Influence; Pilot Projects; Preschool Children